Brain GABA levels are reduced in alcoholic liver disease: A proton magnetic resonance spectroscopy study. (18th December 2018) - Morley, Kirsten C.; Lagopoulos, Jim; Logge, Warren; Baillie, Andrew; Adams, Claire; Haber, Paul S.
Abstract: Background and aims: Baclofen, a selective γ‐aminobutyric acid (GABA)B receptor agonist, has emerged as a potential treatment for alcohol use disorder with much unexplained variation in response to treatment efficacy and dose regimen. Several positive studies include patients with alcoholic liver disease (ALD) and/or history of heavy drinking. The aim of this paper was to examine the association of cortical GABA+ concentration with severity of liver disease (including markers of liver injury) and other clinical characteristics in alcohol patients. Methods: Proton magnetic resonance spectroscopy ( 1 H‐MRS), from the parietal lobe, was analyzed to yield absolute concentration of GABA in 24 alcohol‐dependent individuals. Diagnosis of ALD, markers of liver injury, severity of liver disease (Model for End‐Stage Liver Disease [MELD]), and alcohol history were assessed. Covariates included concurrent medication, age, and recent alcohol consumption. Results: Multiple linear regression revealed that GABA+ concentration was significantly predicted by MELD scores ( F = 5.02, R 2 = 0.59, P = 0.01; MELD: B = −0.63, P = 0.02), when controlling for covariates concurrent medication, age, and recent alcohol consumption. Conclusion: Severity of ALD is associated with lower cortical concentrations of GABA+. These results may explain variations in response to the GABAB agonist, baclofen, in the alcohol‐dependent population. Abstract : Proton magnetic resonance spectroscopy was used to analyze brain GABA+ concentrations in alcohol‐dependent individuals. Severity of ALD was associated with lower cortical concentrations of GABA+. These results may explain variations in response to the GABAB agonist, baclofen, in the alcohol‐dependent population.